A rare case of reel syndrome: The unexpected permanent pacemaker event - Irmansyah, Yos Akbar; Irnizarifka (Heart Science Journal, 2025)
BACKGROUND: "Reel syndrome" is a rare complication that occurs after implantation, affecting up to 1.7% of patients with large generator pockets. This condition generally manifests 4–6 weeks post-implantation. CASE ILLUSTRATION: A 64-year-old woman presented unexpectedly with exertional dyspnea and mild fatigue over the past two days. She has a history of pacemaker installation from one month ago. The ECG demonstrated loss of capture, and pacemaker interrogation showed increased capture thresholds with normal impedance. A chest X-ray revealed a ventricular lead coil encircling the generator with lead dislodgment. Reel syndrome is defined by the torsion of the pulse generator along its transverse axis, leading to the coiling of the pacemaker leads around it, which typically protects both the generator and the leads from damage. Symptoms remain asymptomatic until lead dysfunction occurs due to lead malposition. We suggest appropriate diagnostic assessments, such as chest X-rays and ECGs, for prompt identification. The older population has been recognized as a considerable risk factor for this "event." CONCLUSION: Upon confirmation, reel syndromes require immediate intervention. Effective implantation techniques and information for patients and caregivers are essential in alleviating these issues.